Improving Quality and Curbing Health Care Spending: Opportunities for the Congress and the Obama Administration - Wennberg, John E.; Brownlee, Shannon; Fisher, Elliott S.; Skinner, Jonathan S.; Weinstein, James (2008)
Rising health care costs are a major challenge to the American economy, particularly at a time of deepening recession and a renewed commitment to extend coverage to the uninsured. Dartmouth Atlas research on geographic differences in health care delivery and spending points to an opportunity to achieve significant savings in health care costs without compromising health care quality and outcomes. More spending and more utilization do not translate into improved life expectancy for those with chronic illness. The differences in the use of discretionary surgery do not reflect differences in patient preferences and informed patient choice. This paper discusses opportunities for Congress and the Obama Administration to address key shortcomings in our health care system that result in unwarranted geographic variation and uncontrolled growth in health care spending. Success in this effort will not only improve the quality of care, it will make it possible to extend coverage to America’s uninsured without inducing a major increase in health care spending.